Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12979-016-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

HCV monoinfection and HIV/HCV coinfection enhance T-cell immune senescence in injecting drug users early during infection

Abstract: BackgroundInjecting drug users (IDU) are at premature risk of developing multimorbidity and mortality from causes commonly observed in the elderly. Ageing of the immune system (immune-senescence) can lead to premature morbidity and mortality and can be accelerated by chronic viral infections. Here we investigated the impact of HCV monoinfection and HIV/HCV coinfection on immune parameters in (ex-) IDU. We analyzed telomere length and expression of activation, differentiation and exhaustion markers on T cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…An acute telomere shortening early on in the HIV infection course has been previously reported. 13 Telomere shortening during HIV seroconversion has also been reported in a smaller sample (n = 31), using a different telomere length assay and an extended time gap (2 years) between preseroconversion and postseroconversion sampling. 16 Our study confirms this and demonstrates that rapid telomere shortening occurs quickly after HIV seroconversion, and faster than after HCV seroconversion.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An acute telomere shortening early on in the HIV infection course has been previously reported. 13 Telomere shortening during HIV seroconversion has also been reported in a smaller sample (n = 31), using a different telomere length assay and an extended time gap (2 years) between preseroconversion and postseroconversion sampling. 16 Our study confirms this and demonstrates that rapid telomere shortening occurs quickly after HIV seroconversion, and faster than after HCV seroconversion.…”
Section: Discussionmentioning
confidence: 83%
“…12 In addition, a history of hepatitis C virus (HCV) infection has been associated with shorter telomeres in both HIV-infected and uninfected individuals. 4,13 A recent study reported that although telomere length in HIV-infected individuals was shorter than that in uninfected persons, the slope of telomere length vs. age was no different, suggesting an acute shortening early on during the course of infection. 11 Our aim was to measure telomere length before and immediately after HIV and/or HCV seroconversion and explore whether apparent telomere shortening occurs immediately after HIV/HCV seroconversion, or rather over time throughout the chronic infection period.…”
Section: Introductionmentioning
confidence: 99%
“…During chronic viral infections, however, T cells are always dysregulated and often non-responsive to vaccines 1 . We and others have previously reported that T cells from chronically virusinfected individuals are prematurely aged due to accelerated telomere erosion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , but the underlying mechanisms for T cell telomeric DNA damage remain unclear. Since Top2α is required to remove DNA supercoiling generated during cell proliferation, and Top2cc can become trapped during gene transcription to cause Top2cc-linked PDB due to TDP2 depletion 21,22 , we hypothesized that DNA topology in T cells may be affected during viral infections to trigger DDR as a mechanism of virus-induced immune evasion, and thus, persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…T cells play a critical role in control of viral infection. In studying the role of T cell dysregulation in viral persistence in humans, we and others have previously shown that chronic viral infections can cause premature T cell aging and immune senescence, as evidenced by the expression of aging markers and particularly, accumulation of DNA damage [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . However, the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…When telomere lengths were followed over 15 years in individuals infected with HCV or dual HCV/HIV, researchers found differences in telomere lengths compared to lengths of non-HCV-infected individuals [ 81 ]. Telomere lengths in CD4+ T cells were shorter in HCV-infected individuals and shorter in both CD4+ and CD8+ T cells in dual infection.…”
Section: Telomere Dynamics and T-cell Exhaustion During Chronic/prmentioning
confidence: 99%